Analysis of Efforts to Settle Problem Financing in Murabahah Contract at Kospin Bulakamba Sharia Services - Karwanto, Karwanto (Jurnal Konstatering, 2023)
This research is about "Analysis of Troubled Financing Settlement Efforts in Murabahah Contracts at the Bulakamba Sharia Service Kospin Brebes" with the problem of what are the procedures for solving problem financing in murabahah contracts at the Bulakamba Sharia Services Kospin Brebes? This research is a descriptive research with a sociological juridical approach. The types of data used are primary data and secondary data by collecting primary data through observation and interviews while collecting secondary data through literature studies and the theory used is the theory of legal certainty and the theory of legal protection. Keywords: Financing; Contract; Murabaha.